Answer:
y=14+(2/3x)
Step-by-step explanation:
Your main goal is to get Y by itself on one side.
To start subtract 2x from both sides. This will give you -3y=42-2x.
Then you divide both sides by -3 to get Y by itself.
That will leave you with ...
y=14+(2/3x)
(remember the negatives cancel each other out)
You can multiply the equation in any order.
2[-3/9]=[-3/9]2
Commutative Property of Multiplication
Answer:
f(x) = x3 + 3x2 − 4x − 12
Step-by-step explanation:
A polynomial which falls tot he left and rises to the right is a function with a positive leading coefficient. Its formed by the x-intercepts or zeros x = -3, -2 and 2. The zeros form the factors (x+3)(x+2)(x-2). Multiply the factors using the distributive property to find the function in standard form.
(x+3)(x+2)(x-2)
(x^2 + 3x + 2x + 6)(x-2)
(x^2 + 5x + 6)(x-2)
x^3 + 5x^2 + 6x -2x^2 - 10x - 12
x^3 + 3x^2 - 4x - 12
Population mean = (7+8+6+6+6+4+4+1+2+7+6+1+1+1+3+3+5+4+5+7) / 20 = 87/20 = 4.35 <==
sample mean = (4+5+7) / 3 = 16/3 = 5.33 <==